Structural Elements in Canadian Cuisine - Jacobs, Hersch (Cuizine, 2009)
AbstractFood is often an intrinsic element of national identity and pride, but articulating what constitutes a Canadian cuisine has proven elusive. The challenge lies in the absence of a coherent hegemony, an absence arising from a diverse immigrant population and a political tradition that respects its differences. Nonetheless, the notion of a Canadian cuisine finds expression in the country’s public and private institutions, in the way that recipes originating elsewhere have been interpreted, and in the use of native ingredients and practices.